Prevalence of Psittacine Beak and Feather Disease Virus and Avian Polyomavirus in Captivity Psittacines from Costa Rica - Gutiérrez-Espeleta, Gustavo (2013)
Psittacine beak and feather disease virus (PBFDV) and avian polyomavirus (APV) are the most common viral diseases in psittacine birds, both affecting feathers and physical appearance of birds. Between 2005 and 2009, a total of 269 samples were collected from birds presented at veterinary clinics, shelters and rescue centers of wildlife in Costa Rica. They belonged to 19 species of psittacine birds. The most representative species in the sample were Ara macao (157), Ara ambigua (37), Amazona autumnalis (24), Amazon ochrocephala (21) and Ara ararauna (8). A prevalence of 19.7% (53/269) for PBFDV and 4.8% (13/269) for APV was determined using Polymerase Chain Reaction (PCR). In 3.3% (9/269) of the birds mixed infections were detected. Statistical analysis determined that psittacines living in shelters and rescue centers had a greater risk to be positive to PBFDV and APV than birds that were presented at veterinary clinics, while only for PBFDV it was determined, that it is more likely to detect it in feathers than in blood. Finally, birds in-fected with PBFDV had 6.24 times more probability to become infected with APV, than non-infected birds. This is the first report of prevalence of PBFDV and APV in captive psittacines from Costa Rica.